When the President Endorses the Nation’s Next Leader: Detecting the Concept of Power in Javanese Culture Through Presidential Communication - Widodo, Ari Santoso; Dani, Rendro (Warta Ikatan Sarjana Komunikasi Indonesia, 2023)
This article examines how President Joko Widodo (Jokowi) exercises his power through his presidential communication. It focuses on Jokowi’s statement when he endorses presidential candidates by using simple language, codes, and symbols. The purpose of this study is to decipher the possible meaning within the statement of Jokowi regarding his endorsement of presidential candidates. It also attempts to contextualize it within the larger setting of political public relations by using soft propaganda techniques. This study uses a qualitative case study approach that uses the lens of Benedict Anderson’s concept of power in Javanese culture and Eric Louw’s premise about the hype maker or messenger. Researchers argue that Jokowi's communication, in this case, can be interpreted as a political game where the president tries to show his power by deliberately violating political procedures to remove uncertainty among the political elite. The president’s power may also be seen in his soft propaganda communication, which employs “oversimplification” and “logical fallacies” techniques to stir up public emotion and resonance in the media and political elite. This article offers some critical insights on presidential communication strategy from different perspectives, particularly through the concept of power in the Javanese culture, the president’s role as a hype maker, and how political public relations strategies can be harnessed to modify a political process.